Insider trading under trading ban regulation in China's A-share market - Chafen Zhu; Li Wang (China Journal of Accounting Research, 2015)
This study examines the effects of China's 2008 trading ban regulation on the insider trading of large shareholders in China's A-share market. It finds no evidence of insider trading during the ban period (one month before the announcement of a financial report), due to high regulation risk. However, the ban only constrains the profitability of insider trades during the ban period, while trades outside it remain highly profitable. Informed insider trading before the ban period is 2.83 times more profitable than uninformed trading. The regulation has changed insider trading patterns, but has been ineffective in preventing insider trading by large shareholders due to rigid administrative supervision and a lack of civil litigation and flexible market monitoring. This study enhances understanding of large shareholders' trading behavior and has important implications for regulators.
Keywords: G38; G18; 650; Insider trading; Trading ban regulation; Large shareholders' trading; Earnings announcement